IMPLEMENTATION OF LEGAL PROTECTION ON WOMEN VICTIMS OF DOMESTIC VIOLENCE - Abdul Kadir; Tiara Putri; Almirah Shalwa; Sephia Wahyuni; Regita Nurcahyani; Salwa Salsabila (Universitas Muhammadiyah Tangerang, 2021)
The laws and regulations have the provisions for illegal acts or crimes which include domestic violence. Domestic violence is a form of special crime. This study examines the form than implementing legal protection for women victims of domestic violence based on the criminal justice system in Indonesia as well as how the obstacles that arise in this regard. The existence of Law Number 23 of 2004 concerning the elimination of domestic violence is expected to be able to provide legal protection for victims of domestic violence significantly, in this case are women. The results showed that the decision Number: 519 K/Pid.Sus/2020 as an example of the implementation of legal protection for wives as victims is appropriate. In relation to the obstacles that arise, among others, law enforcement officers who have various understandings regarding domestic violence, difficulties for legal officers in implementing Law No. 23 of 2004, lack of courage to report incidents of domestic violence from victims, and difficulties in proving the problem of domestic violence.Keywords: Domestic violence, protection, implementation, women